Interactive Theorem Proving Second International Conference, ITP 2011, Berg en Dal, The Netherlands, August 22-25, 2011. Proceedings - Eekelen, Marko; Geuvers, Herman; Schmaltz, Julien; Wiedijk, Freek; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Interactive Theorem proving, ITP 2011, held in Berg en Dal, The Netherlands, in August 2011. The 25 revised full papers presented were carefully reviewed and selected from 50 submissions. Among the topics covered are counterexample generation, verification, validation, term rewriting, theorem proving, computability theory, translations from one formalism to another, and cooperation between tools. Several verification case studies were presented, with applications to computational geometry, unification, real analysis, etc.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Logics and Meanings of Programs; Software Engineering; Mathematical Logic and Formal Languages; Programming Languages, Compilers, Interpreters; Artificial Intelligence (incl. Robotics).; Programming Techniques